Megenal Varian Baru Virus Covid-19 (Omicron) Dan Meningkatkan Kesadaran Masyarakat Tentang Pentingnya Vaksinasi Covid-19: Knowing the New Variant of the Covid-19 Virus (Omicron) And Raising Public Awareness About the Importance of Covid-19 Vaccination - Andi Khairul; Imtihana; Dewi Febrianti; Nober Pasiga; Dian Putri (Yayasan Habiburrahman Jamalu Bina Ummat, 2022)
The virus that causes COVID-19, SARS-CoV-2 continues to mutate to form new variants. The latest variant that has been detected in the Omicron variant known as variant B.1.1.529. The Omicron variant has a high transmission speed of up to 5 times the previous variant, including the Delta variant. The speed of transmission that occurred in South Africa is still being studied epidemiologically to determine whether this is caused by Omicron or other factors. Transmission is easier in individuals who have not received the vaccine and it can also cause complications in treatment. However, some countries are concerned that there will be pressure on the health system due to an increase in the need for hospitalization because the transmission rate of this variant is much higher. Virus replication occurs 70 times faster in the respiratory tract, but 10 times slower in human lung tissue. Because one of the efforts that can be done to avoid Covid-19 is to use a vaccine, it can help protect the people around you from the coronavirus. Especially people who are at high risk of developing severe illness due to COVID-19. By looking at this problem, there is a need for health education in recognizing the new variant of Covid-19 (omicron) and increasing public awareness of the importance of the Covid-19 vaccination.